2016
DOI: 10.5123/s2176-62232016000500014
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos ecológicos da fauna de flebotomíneos em focos de leishmaniose na Amazônia Oriental, Estado do Pará, Brasil

Abstract: RESUMOEste estudo descreve comunidades de flebotomíneos e suas variações sazonais em focos de transmissão das leishmanioses na interface urbano-rural do município minerário de Juruti, Estado do Pará, na Região Amazônica. Realizou-se captura mensal de flebotomíneos durante dois anos, em duas localidades sentinelas, Santa Maria e Paraense. Armadilhas CDC foram colocadas no intra e no peridomicílio. A amostra de 36.408 flebotomíneos teve 32 espécies representadas; as mais frequentes foram Lutzomyia longipalpis (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…Pilões, Alagoa Grande, Alagoa Nova e Areia, são municípios que pertencem ao Agreste paraibano, uma zona típica de transição natural, influenciada pela semiaridez do sertão e umidade vinda do litoral, apresentando adensamento populacional, chuvas regulares e variações de temperaturas, com a presença da policultura em muitas propriedades, predominando a plantação de cana de açúcar e atividades agropecuárias (Moreira, 1989). O clima e o acúmulo de matéria orgânica proveniente da atividade agrícola são atributos essenciais para atrair vetores, que se reproduzem perto de domicílios e essa proximidade aos habitantes é um fator fundamental para a transmissão da doença (Chagas et al, 2016;Menezes et al, 2016). No ano de 2019, Sapé e Cruz do Espirito Santo apresentaram 42,25% das notificações desse ano, sem ter notificado nenhum caso nos anos anteriores, o que sugere um surto na microrregião desses municípios.…”
Section: Resultsunclassified
“…Pilões, Alagoa Grande, Alagoa Nova e Areia, são municípios que pertencem ao Agreste paraibano, uma zona típica de transição natural, influenciada pela semiaridez do sertão e umidade vinda do litoral, apresentando adensamento populacional, chuvas regulares e variações de temperaturas, com a presença da policultura em muitas propriedades, predominando a plantação de cana de açúcar e atividades agropecuárias (Moreira, 1989). O clima e o acúmulo de matéria orgânica proveniente da atividade agrícola são atributos essenciais para atrair vetores, que se reproduzem perto de domicílios e essa proximidade aos habitantes é um fator fundamental para a transmissão da doença (Chagas et al, 2016;Menezes et al, 2016). No ano de 2019, Sapé e Cruz do Espirito Santo apresentaram 42,25% das notificações desse ano, sem ter notificado nenhum caso nos anos anteriores, o que sugere um surto na microrregião desses municípios.…”
Section: Resultsunclassified
“…The climatic conditions in the municipality of Seropédica do not present significant changes, remaining constant for several months of the year and at favourable temperature, humidity and precipitation levels for the development of the sand flies, which remained present during all months. Chagas et al (2016) observed the presence of sand flies all year round in Pará state, Brazil, but they reported a correlation between abiotic factors (rainy season) and the number of sand flies and related the increase in relative humidity with more activity of the adult sand flies. The study by Meneguzzi et al (2016), in southeastern Brazil, reported that all sand flies species showed high sensitivity to temperature and precipitation, unlike the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Chagas et al . (2016) observed the presence of sand flies all year round in Pará state, Brazil, but they reported a correlation between abiotic factors (rainy season) and the number of sand flies and related the increase in relative humidity with more activity of the adult sand flies. The study by Meneguzzi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Infectious forms of Leishmania infantum have already been identified in this species by many authors (Lainson et al 1987;Michalsky et al 2011;Lidani et al 2017). Due to its great ecological value and adaptive plasticity, it is currently considered an urbanized species, being captured mainly at home and in shelters for domestic animals (Barata et al 2005;Dias et al 2007;Michalsky et al 2009;Chagas et al 2016). However, the record of Lu.…”
Section: Discussionmentioning
confidence: 99%